Biogas upgrading with carbon capture and energy recovery enhancement - Chan, Hui Ling (Nanyang Technological University, 2024)
Biological H2-assisted biogas upgrading has gained significant attention as an environmentally friendly substitute to common physico-chemical upgrading techniques. It involves the use of the microorganisms present within the AD system to convert H2 and resultant CO2 in the biogas to CH4, with the goal of upgrading the energy content in biogas to that of biomethane quality (> 95% CH4). Numerous studies have encountered challenges in achieving the desirable biogas quality, primarily attributed to the limited solubility of H2. Microbes can only utilize dissolved H2, thus making its solubility a crucial factor influencing the efficiency of biogas upgrading processes. This thesis investigated several methods of biological biogas upgrading - they included the use of direct diffuser-based injection with biogas recirculation and prolonged microbial acclimatization for ex-situ and in-situ biogas upgrading to determine the efficiency of conventional methods for H2 gas to liquid transfer. It was observed particularly for in-situ biogas upgrading, where the AD was more susceptible to VFA shocks and inhibition with high H2 partial pressure, the achieved biogas quality was limited to 84% CH4 content. Thus, this study designed and evaluated a novel ceramic membrane contactor module for H2 injection. The results show that H2 dissolution was able to maintain at high efficiency by controlling gas supply and sludge recirculation rate, achieving a biogas quality of average 98.8% CH4 during the stable operation phase with a 107.5% increase in the CH4 production rate. This also outperforms conventional H2 injection using diffuser sparging as well as ex-situ biogas upgrading methods. Microbial community analysis found high Methanobacterium spp. abundance within the archaea at 95.2% at the end of the operation, allowing the dominance of the hydrogenotrophic methanogenesis pathway for high upgrading efficiencies. The system is further advantaged as an external connecter module that can be easily coupled to common commercial anaerobic digestion systems for biogas upgrading.